DEBT TO EQUITY RATIO (DER) DAN TOTAL ASSET TURNOVER (TATO) DALAM MENENTUKAN HARGA SAHAM PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI TAHUN 2018-2021 DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING - Putri Kifti Maulana; Alfiatul Maulida (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
The purpose of this study was to analyze and test the Debt to Equity Ratio (DER) and Total Asset Turnover (TATO) on stock prices with dividend policy as an intervening variable. This research uses quantitative research methods. The population in this study are companies listed on the LQ45 Index with a sample of 8 companies. The sampling technique uses non-probability sampling techniques with purposive sampling techniques. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that Debt to Equity Ratio has a significant positive effect on dividend policy, Total Asset Turnover has a significant positive effect on dividend policy, Debt to Equity Ratio has a positive effect but not significant to stock prices, Total Asset Turnover has a significant positive effect on stock prices, dividend policy has a significant positive effect on stock prices. The results of the indirect effect hypothesis test show that the Debt to Equity Ratiovariable on stock prices through dividend policy has a significant positive effect, Total Asset Turnover on stock prices through dividend policy has a significant positive effect.